Service Quality and Students' Satisfaction in Public Higher Education Institutions During Covid-19 in Malaysia - Uma Mageswary, Krishnan; Wong, Chee Hoo (INTI International University, 2021)
The COVID-19 pandemic has been a challenging time for Malaysians. The pandemic hurts many sectors, especially education. When Malaysia's Prime Minister, Tan Sri Muhyiddin Yassin, announced the Movement Control Order effective 18th March 2020, all sectors related to education, nurseries, government and private schools, international schools and higher education institutions were closed. The purpose of this study is to survey students on whether service quality has a significant impact on student satisfaction during COVID-19 in Malaysia. This research was a descriptive study with the cross-sectional method. Survey with Likert scales will be used to get the feedback from respondents from Public Higher Education Institution. The data collected from 257 respondents were analyzed with SPSS software. The study utilised SERVQUAL measurement to distinguish whether service quality's dimensions of reliability, responsiveness, tangibles, assurance, and empathy significantly influence the undergraduate student satisfaction in Public Higher Education Institutions in Malaysia. This study is novel that it was one of the first customer satisfaction studies during Covid-19, and it is hoped that the findings will be of pivoting reference by the practitioner and the researchers alike.